Multisource Evaluation of Surgeon Behavior Is Associated With Malpractice Claims. Issue 1 (July 2019) - Lagoo, Janaka; Berry, William R.; Miller, Kate; Neal, Brandon J.; Sato, Luke; Lillemoe, Keith D.; Doherty, Gerard M.; Kasser, James R.; Chaikof, Elliot L.; Gawande, Atul A.; Haynes, Alex B.
Abstract : Objective: We merged direct, multisource, and systematic assessments of surgeon behavior with malpractice claims, to analyze the relationship between surgeon 360-degree reviews and malpractice history. Background: Previous work suggests that malpractice claims are associated with a poor physician-patient relationship, which is likely related to behaviors captured by 360-degree review. We hypothesize that 360-degree review results are associated with malpractice claims. Methods: Surgeons from 4 academic medical centers covered by a common malpractice carrier underwent 360-degree review in 2012 to 2013 (n = 385). Matched, de-identified reviews and malpractice claims data were available for 264 surgeons from 2000 to 2015. We analyzed 23 questions, highlighting positive and negative behaviors within the domains of education, excellence, humility, openness, respect, service, and teamwork. Regression analysis with robust standard error was used to assess the potential association between 360-degree review results and malpractice claims. Results: The range of claims among the 264 surgeons was 0 to 8, with 48.1% of surgeons having at least 1 claim. Multiple positive and negative behaviors were significantly associated with the risk of having malpractice claims ( P < 0.05). Surgeons in the bottom decile for several items had an increased likelihood of having at least 1 claim. Conclusion: Surgeon behavior, as assessed by 360-degree review, is associated with malpractice claims. These findings highlight the importance of teamwork and communication in exposure to malpractice. Although the nature of malpractice claims is complex and multifactorial, the identification and modification of negative physician behaviors may mitigate malpractice risk and ultimately result in the improved quality of patient care. Abstract : Supplemental Digital Content is available in the text